2013
DOI: 10.1111/nmo.12204
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal recruiting and activation profiles in peripheral blood mononuclear cells in response to pathogen‐associated molecular patterns stimulation in patients with IBS

Abstract: Background Immune activation, increased Toll‐like Receptors (TLR) expression, and gut epithelial diffusion of bacterial molecules have been reported in irritable bowel syndrome (IBS). Thus, we sought to relate these factors by analyzing gut homing (integrin α4β7), intestinal recruiting (CCR5) and activation (CD28) phenotypes, and the cytokines and chemokines concentration in peripheral blood T‐lymphocytes stimulated with TLR‐ligands. Methods Twenty‐one IBS‐Rome II (1 PI‐IBS) patients and 19 controls were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
1
13
0
3
Order By: Relevance
“…In regard to the link between chronic inflammation and carcinogenesis, the mononuclear cells appear to be persuasive warriors expressing a vivid phagocytic capacity [14] , to encompass Toll-like receptors able to recognize pathogen molecules and to be capable to modulate both innate and adoptive immune responses [15][16][17] . Studies have shown that the number of Th1 and Th17 cells is increased in patients with inflammatory bowel disease and correlates well with its severity [18] , whereas the number of CD14 + and CCL11 + mononuclear cells has been found to be increased in colonic biopsies from patients with ulcerative colitis [19] .…”
Section: Peripheral Blood Mononuclear Cells and Cytokine Productionmentioning
confidence: 99%
“…In regard to the link between chronic inflammation and carcinogenesis, the mononuclear cells appear to be persuasive warriors expressing a vivid phagocytic capacity [14] , to encompass Toll-like receptors able to recognize pathogen molecules and to be capable to modulate both innate and adoptive immune responses [15][16][17] . Studies have shown that the number of Th1 and Th17 cells is increased in patients with inflammatory bowel disease and correlates well with its severity [18] , whereas the number of CD14 + and CCL11 + mononuclear cells has been found to be increased in colonic biopsies from patients with ulcerative colitis [19] .…”
Section: Peripheral Blood Mononuclear Cells and Cytokine Productionmentioning
confidence: 99%
“…Secondly, we did not determine any differences between subjects with PI-IBS and those without a history of gastrointestinal infections as a triggering factor for IBS. However, it should be noted that PI-IBS frequency is very low in Mexico (35). We also did not rule out the presence of celiac disease or inflammatory bowel disease in these subjects, which could have modified the frequency of the polymorphisms studied.…”
Section: Discussionmentioning
confidence: 79%
“…14 Deregulated β7-mediated T lymphocytes homing was observed also in patients with gastrointestinal disorders, such as irritable bowel syndrome (IBS) [15][16][17] and functional dyspepsia. 18 Although these conditions impair patients' quality of life, nutritional interventions and/or functional foods (containing prebiotics, probiotics and/or nutraceuticals) rather than drug treatments should be recommended.…”
Section: -mentioning
confidence: 99%